Identifikasi Faktor Risiko Peningkatan Kejadian Hipertensi - Rachmawati, Fathin Aulia; Setyawan, Febri Endra Budi; Wartiningsih, Minarni (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
Hypertension is recognized as a non-communicable disease and accounts for one in eight deaths worldwide. Hypertension can be diagnosed and treated early through population-based screening and control of behavior and lifestyle changes. The aim of this study was to identify risk factors for increased incidence of hypertension, which could be targets for future intervention. This research uses systematic review methods from various national and international journals, where 30 references were obtained through searches in PubMed, Research Gate, Science Direct, Google Scholar, and the Cochrane library which have been published in the last 5 years. There are several risk factors that increase the prevalence of hypertension such as age, gender, family history (genetics), education, obesity, diabetes, diet, alcohol, smoking, physical activity and stress. There are many risk factors that increase the incidence of hypertension, including old age, gender, family history of hypertension, low awareness and knowledge, obesity, diabetes, poor dietary habits such as increasing salt and fast food intake, alcohol consumption, minimal physical activity, smoking and stress. This is significantly correlated with the incidence of hypertension which can be reduced by controlling risk factors. Hypertension is a public health problem that is not well controlled. Almost half of the population is still unaware of their condition. Intervention planning such as increasing screening coverage, education, public awareness about hypertension, physical activity and healthy living behavior is needed to improve hypertension control. Reducing alcohol consumption, stress and smoking is also necessary. This intervention will be useful as a preventive measure in fighting hypertension.